PELATIHAN PRAKTIKUM SAINS BAGI GURU DAN SISWA DI SEKOLAH DASAR NO. 038/IX KOTO LOLO - Siregar, Anggi Desviana; Mairisiska, Titin; Lala, Kiki; Febrianti, Amelia (Institut Agama Islam Negeri Kerinci, 2024)
Science learning in Elementary Schools (SD) emphasizes the process through practical activities. Still, the SD 038/IX Koto Lolo teachers do not yet involve science practicums in their learning methods. Partners face several obstacles, such as teachers' lack of knowledge regarding the importance of implementing practicums, unfamiliar with using practicum tools and materials, and not understanding the procedures for implementing science practicums in elementary schools. To overcome this problem, service activities are carried out through comprehensive training, which begins with an understanding of the urgency of science practicum in elementary school, a demonstration of several examples of elementary school science practicum, and direct practice according to the instructions that have been explained. As a result, training participants gained four things, namely: a) Knowledge, where they gained new knowledge about implementing elementary science practicum; b) Ability (Skill), participants appear to have the skills to carry out elementary science practicum activities; c) Behavior (Attitude), from the practicum carried out, a scientific attitude is formed from the participants; d) Product, elementary school teachers produce science practicum guides in the form of simple modules that can be applied in elementary schools.